Evaluation of Knowledge and Awareness of Aspergillosis Infections among Healthcare Workers - Al. Ibraheem, Shrouk A. Hassan; Seiwan, Anwar Nather; Mohammed, Hanan A. (American Journal of Biology and Natural Sciences, 2025)
Background: Aspergillus is a common saprophytic conidial fungus found in soil. Fungal infections caused by Aspergillus can have a wide range of clinical manifestations depending on the immunological state of the patient. Aspergillus can primarily affect the lungs and cause diseases such as allergic bronchopulmonary aspergillosis (ABPA), chronic pulmonary aspergillosis (CPA), and invasive pulmonary aspergillosis (IPA) ABPA the patients affected with asthma and cystic fibrosis, while CPA affects patients with underlying وlung conditions. IPA has a high mortality rate and can occur in patients without obvious immune compromise. Objective: The study aimed to evaluate the knowledge of healthcare workers about aspergillosis using a quantitative and descriptive approach with an electronic questionnaire. Methods: A descriptive cross-sectional study and non-probability convenience sampling were randomly conducted for 149 HCWs. This sample was distributed throughout twenty hospitals and twenty-five healthcare workers centers, conducted from March to July 2022. Data was gathered and analyzed using both descriptive and inferential statistics using electronic questionnaires. Results: The findings indicate that only 13% of healthcare workers had good knowledge about aspergillosis, while 60% had acceptable knowledge and 27% had poor knowledge. Statistically significant differences were found in the answers of healthcare workers for all questions except one. The study also found significant differences in knowledge between males and females, profession, and working unit. Conclusions: These findings highlight the need for educational programs and training for healthcare workers to improve their knowledge about aspergillosis, which can ultimately lead to better patient care and outcomes. In summary, it is essential that healthcare workers understand the risks that aspergillosis disease poses to their health and the importance of following appropriate safety protocols, including the use of PPE, to minimize exposure to fungal spores. They must also be well-versed in identifying the symptoms of the condition so that they can diagnose and treat it promptly.